Co-authors, colleagues, and contributors: Complications in collaboration and sharing lessons on academic writing - Harvey, Orlanda; van Teijlingen, Alexander; Regmi, Pramod R; Ireland, Jillian; Rijal, Aney; van Teijlingen, Edwin (Health Prospect, 2022)
Academic writing, especially in the health field, is usually an interdisciplinary team effort. This paper highlights some of the trials, tribulations, and benefits of working with co-authors. This includes collaborations and co-authorship between academics from different disciplines, academics of different level of careers, and authors from countries of varying economies i.e., high-income countries (HICs) and from low-and middle-income countries (LMICs). This paper also provides advice in the form of several useful tips to lead authors and co-authors to support collaborative working.